Gender. - Evans, Mary (Routledge key guides., 2013)
This invaluable volume provides an overview of 37 terms, theories and concepts frequently used in gender studies which those studying the subject can find difficult to grasp. Each entry provides a critical definition of the concept, examining the background to the idea, its usage and the major figures associated with the term. Taking a truly interdisciplinary and global view of gender studies, concepts covered include:Agency Diaspora Heteronormativity SubjectivityPerformativity Class Feminist Politics Body G.